An Analysis of Brand Awareness Influence on Purchase Intention in Bandar Lampung City S Online Transportation Service (Study on Y Generation Consumers) - Pandjaitan, Dorothy Rouly Haratua (Economics and Business Solutions Journal, 2019)
A brand has a value that is delivered to the consumer. Services are everything that the consumers want to use and enjoy. In the transportation service industry, the best service is to create value services that can attract consumers to use the service. The object of ths study is consumers from the Y Generation. The Y Generation is a society group whose members are 26 years old and above, where the main two factors in relation to their needs is comfort and security. The Go-Jek brand is a well-known transportation services brand throughout Indonesia. The conclusion of this study is the high brand value of Go-Jek brand is increases the intention of using Gojek services especially from the Y Generation consumers. The implication of this study is that Go-Jek Company must utilise Y Generation consumer needs such as comfort and an alternative path for travelling so then the consumer can arrive at the destination faster.